Application of Guar Gum and its Derivatives as Green Binder/Separator for Advanced Lithium‐Ion Batteries. Issue 2 (1st February 2022) - Kaur, Simran; Santra, Soumava
Abstract: Since their first commercialization in the 1990s, lithium‐ion batteries (LIBs) have become an indispensible part of our everyday life in particular for portable electronic devices. LIBs have been considered as the most promising sustainable high energy density storage device. In recent years, there is a strong demand of LIBs for hybrid electric and electric vehicles to lower carbon footprint and mitigate climate change. However, LIBs have several issues, for example, high cost and safety issues such as over discharge, intolerance to overcharge, high temperature operation etc. To address these issues several new types of electrodes are being studied. Traditional binder PVDF is costly, difficult to recyle, undergoes side reactions at high temperature and cannot stabilize high energy density electrodes. To overcome these challenges, diiferent binders have been introduced with these electrodes. This minireview is focused on the application of guar gum as a binder for different electrodes and separator. The electrochemical performance of electrodes with guar gum has been compared with other binders. Abstract : Bind naturally to perform : Adoption of suitable binder imparts remarkable effect on the electrochemical performance of electrodes in LIBs. Binders can alleviate several issues faced by different types of electrodes and separators. In this review, electrochemical performance of different electrodes for LIBs and separator with an abundant, low‐cost, renewable, green binder guar gum as well as its derivatives have been discussed and compared with other binders, for example, PVDF.